2016
DOI: 10.1039/c5sc03761a
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acid–DMAPO cooperative catalysis for dehydrative condensation between carboxylic acids and amines

Abstract: Arylboronic acid and DMAPO cooperatively catalyse the dehydrative condensation reaction between carboxylic acids and amines to give the corresponding amides under azeotropic reflux conditions. This cooperative use is much more effective than their individual use as catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…6 ) ( 37 ). The synthesis of phenylacetamide 10 is ubiquitous in the amidation literature, so this compound was selected for comparison ( 12 24 , 38 ). Pleasingly, our procedure showed clear improvements over existing catalytic amidation methods with regard to the PMI for both (i) the reaction conditions (more concentrated; no additives or molecular sieves) and (ii) the workup (no liquid-phase extraction).…”
Section: Resultsmentioning
confidence: 99%
“…6 ) ( 37 ). The synthesis of phenylacetamide 10 is ubiquitous in the amidation literature, so this compound was selected for comparison ( 12 24 , 38 ). Pleasingly, our procedure showed clear improvements over existing catalytic amidation methods with regard to the PMI for both (i) the reaction conditions (more concentrated; no additives or molecular sieves) and (ii) the workup (no liquid-phase extraction).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1 shows an adapted proposal [21][22][23] for the catalytic cycle using phenylboronic acid as the catalyst to perform the aminolysis reactions between ethyl salicylate ES and the amines Ae-Aj providing the amides S-Ae-Aj, respectively. The catalytic cycle starts with the formation of a cyclic intermediate between PBA and ethyl salicylate ES.…”
Section: Resultsmentioning
confidence: 99%
“…6 Despite the relatively few studies of these compounds, acyloxyborates have found important applications in fire-proofing polymer compositions, as stabilisers for synthetic rubbers, and in the pharmaceutical industry. 7 Related boron carboxylate species have also been proposed as intermediates in dehydrative condensations between a carboxylic acid and an amine using catalysts derived from borate esters [8][9][10] as well as boric, 11 boronic, [12][13][14][15][16][17][18][19][20][21] and borinic acids. 22 Recently however, Whiting and coworkers 23 have suggested an alternative mechanism in which an oxo-bridged bis-boron species, i.e.…”
Section: Introductionmentioning
confidence: 99%